2019
DOI: 10.3389/fimmu.2019.02908
|View full text |Cite
|
Sign up to set email alerts
|

Human Apoptotic Cells, Generated by Extracorporeal Photopheresis, Modulate Allogeneic Immune Response

Abstract: The induction of specific and sustainable tolerance is a challenging issue in organ transplantation. The discovery of the immunosuppressive properties of apoptotic cells in animal models has paved the way for their use in human transplantation. In this work, we aimed to define a stable, reproducible, and clinically compatible production procedure of human apoptotic cells (Apo-cells). Using a clinically approved extracorporeal photopheresis technique, we have produced and characterized phenotypically and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…The induction of regulated cell death in lymphocytes is important for the efficacy of ECP by providing antigenic material and favoring antigen loading and maturation of APCs, thereby eliciting antigen-specific immunoregulation. [9][10][11] Verification of sufficient apoptosis induction is central for quality control of clinical ECP products. 22 Here, singlehigh-dose UVA only (4-5 J/cm 2 ) treatment induced an apoptotic rate with increased kinetics in PBMCs in comparison to standard ECP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The induction of regulated cell death in lymphocytes is important for the efficacy of ECP by providing antigenic material and favoring antigen loading and maturation of APCs, thereby eliciting antigen-specific immunoregulation. [9][10][11] Verification of sufficient apoptosis induction is central for quality control of clinical ECP products. 22 Here, singlehigh-dose UVA only (4-5 J/cm 2 ) treatment induced an apoptotic rate with increased kinetics in PBMCs in comparison to standard ECP.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ECP is reported to induce immunosuppression upon allogeneic T‐cell activation 9 . Thus, monocytes treated with ECP or UVA only successfully reduced allogeneic T‐cell proliferation compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the elusive switch from a predominant Th2 to a Th1 cytokine microenvironment harnessed by ECP, studies addressing the secretory capacity of peripheral blood mononuclear cells of GvHD patients and in vitro models of allogenic reactions revealed that ECP exposure can increase the production of Th2 cytokines including IL-10 and TGF-β [71-73] (Fig. 3).…”
Section: Modulation Of Antigen-specific T-cell Responsesmentioning
confidence: 99%